A human tau seeded neuronal cell model recapitulates molecular responses associated with Alzheimer’s disease - Ficulle, Elena; Kananathan, Sarubini; Airey, David; Gharbi, Severine I.; Humphryes-Kirilov, Neil; Scherschel, James; Dunbar, Charlotte; Eastwood, Brian J.; Laing, Emma; Collier, David A.; Bose, Suchira (Scientific reports, 2022)
Cellular models recapitulating features of tauopathies are useful tools to investigate the causes and consequences of tau aggregation and the identification of novel treatments. We seeded rat primary cortical neurons with tau isolated from Alzheimer’s disease brains to induce a time-dependent increase in endogenous tau inclusions. Transcriptomics of seeded and control cells identified 1075 differentially expressed genes (including 26 altered at two time points). These were enriched for lipid/steroid metabolism and neuronal/glial cell development genes. 50 genes were correlated with tau inclusion formation at both transcriptomic and proteomic levels, including several microtubule and cytoskeleton-related proteins such as Tubb2a, Tubb4a, Nefl and Snca. Several genes (such as Fyn kinase and PTBP1, a tau exon 10 repressor) interact directly with or regulate tau. We conclude that this neuronal model may be a suitable platform for high-throughput screens for target or hit compound identification and validation.